Leleshusia, a new replacement name for Granulina Leleshus, 1975 (Anthozoa: Heliolitoidea) nec Jousseaume, 1888 (Gastropoda: Neogastropoda: Marginellidae) - Doweld, Alexander B. (Zootaxa, 2015)
The genus Granulina (type species Plasmoporella granulosa Bondarenko, 1958, by original designation) was established by Leleshus (1975: 7) for a distinctive heliolitoid genus from the Upper Ordovician of Kazakhstan and Tajikistan. However, the name Granulina Jousseaume, 1888 (p. 191), which designates a genus of a living molluscs (Gastropoda: Neogastropoda: Marginellidae: Granulininae), has priority over the fossil generic name, which is its junior homonym.